Alien in the outfield - Chapman, Helen; Liddell, Mal (Macmillan South Yarra, Vic., 1998)
Alien in the Outfield follows the exciting story of a young baseball player who discovers that his new teammate is not from Earth. When an alien lands on Earth and joins a struggling little league team, their fortunes take a dramatic turn. With the alien's extraordinary abilities and the team's growing friendship, they set out to win the championship. The book blends sports, adventure, and humor while exploring themes of teamwork, acceptance, and the challenges of fitting in, no matter where you're from$1 (Beven if it's another planet!s